One step preparation and electrochemical analysis of IQS, a cell–cell communication signal in the nosocomial pathogen Pseudomonas aeruginosa - Shang, F.; Muimhneacháin, E.; Reen, F.; Buzid, A.; O'Gara, Fergal; Luong, J.; Glennon, J.; McGlacken, G. (Pergamon, 2014)
Pseudomonas aeruginosa uses a hierarchical cell–cell communication system consisting of a number of regulatory elements to coordinate the expression of bacterial virulence genes. Sensitive detection of quorum sensing (QS) molecules has the potential for early identification of P. aeruginosa facilitating early medical intervention. A recently isolated cell–cell communication molecule, a thiazole termed IQS, can bypass the las QS system of P. aeruginosa under times of stress, activating a subset of QS-controlled genes. This compound offers a new target for pathogen detection and has been prepared in a one step protocol. A simple electrochemical strategy was employed for its sensitive detection using boron-doped diamond and glassy carbon electrodes by cyclic voltammetry and amperometry.